"Big push" green industrial policy - Niko Jaakkola; Frederick van der Ploeg; Anthony Venables (EconPol Forum, 2023)
Carbon pricing is a central part of climate policy, but is politically difficult while the economy is still reliant on fossil fuels. The long-lived green investments required to break the carbon lock-in depend on expected taxes, not current taxes. Policies which target the expectations of the private sector can shock the economy and move it onto a green path. Green industrial policy can leverage technological/political feedbacks to kick-start the transition. Fossil fuel bans can help break the technological and political lock-in into carbon reliance.
Keywords: 330